Potencjał intelektualny uczniów z zespołem Downa i orzeczoną niepełnosprawnością intelektualną w opinii ich rodziców - Popowska, Krystyna (Kultura-Społeczeństwo-Edukacja, 2021)
Research was conducted to find out about the parents’ opinions on the intellectual potential of their children with Down syndrome and diagnosed intellectual disability studying in 4–8 grades of common, integration and special schools. Additionally, the factors determining the respondents’ opinions were analyzed. The paper uses the author’s questionnaire was placed on groups for parents of children with Down syndrome on the social network site Facebook. In addition, surveys were sent by e-mail to the primary school districts and non-governmental organizations that help children with Down syndrome. Fifty two questionnaires were collected. The results indicate that, despite intellectual disability, parents recognize the intellectual potential of their children. It can be assumed that assessments of the intellectual potential of students with Down syndrome and diagnosed intellectual disability are determined by their siblings in the intellectual norm, gender, using verbal speech, communication skills, social skills and opinions of their parents about their successes in school and progress as a result of the therapy.